Analisis Kesalahan Berbahasa dalam Penulisan Karangan Teks Narasi Siswa Kelas VII di UPTD SMP Negeri 1 Gunungsitoli - Juwita Putri Laia; Noibe Halawa; Yanida Bu’ulolo; Imansudi Zega (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
The ability of writing essay skills of students in grade VII The use of verbs, sentence structures, use of pronouns and prepositions in writing narrative text essays of students is still lacking. This study aims to analyze language errors in writing narrative text essays of grade VII students at UPTD SMP Negeri 1 Gunungsitoli. This study is a qualitative descriptive study. The data of this study are student worksheets in writing narrative text essays. The data sources in this study were grade VII-A students of UPTD SMP Negeri 1 Gunungsitoli and one of the Indonesian language teachers. The research instruments were documentation in the form of photos, notes, documents, archives and pictures. Data collection techniques were observation, interviews and written tests. Data analysis techniques in this study were data reduction, categorization of language errors, data presentation and drawing conclusions. The results of the study, the errors expressed in the students' narrative text compositions were 87% errors which included: (1) inconsistent verb forms totaling 8 errors, (2) inappropriate verb selection totaling 9 errors, (3) use of passive verbs totaling 14 errors, (4) sentences that are too long and complicated totaling 15 errors, (5) subject and predicate errors increased by 9, (6) errors in the use of punctuation 8, (7) incompatibility between pronouns and their predecessors totaling 5 errors, (8) repeated use of pronouns totaling 6 errors, (9) errors in the choice of prepositions totaling 7 errors and (10) use of unnecessary prepositions totaling 6 errors. The students' ability to write narrative text compositions in the use of verbs totaling 31 errors, structure totaling 32 errors, pronoun sentences and prepositions totaling 24 errors.